2005
DOI: 10.1210/jc.2003-032059
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Changes in Body Weight and Insulin Resistance on Inflammation and Endothelial Function in Morbid Obesity after Bariatric Surgery

Abstract: Metabolic alterations such as insulin resistance are thought to underlie the endothelial dysfunction and low grade inflammation found in morbid obesity. Twenty-six morbidly obese patients, aged 39.0 +/- 10.0 (mean +/- sd), were evaluated before and 4.2 +/- 0.8 months after bariatric surgery. A marked increment in the insulin sensitivity index (S(I)) and the endothelium-dependent vasodilatory response in a dorsal hand vein was observed after weight loss following bariatric surgery. Circulating levels of E-selec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
138
1
4

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 185 publications
(161 citation statements)
references
References 54 publications
18
138
1
4
Order By: Relevance
“…Similar results were obtained by Vázquez et al (2005) in patients with morbid obesity four months after bariatric surgery, which indicated that inflammatory pathways, including the TNF-α system and IL-6, remain activated. However, in 22 obese and 20 hypertensive patients subjected to BT with thermal water at 38 °C in 15 sessions (each of 30-min duration), Oláh et al (2011) observed a significant decrease in post-treatment CRP levels in a hypertensive group but not in obese subjects.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Similar results were obtained by Vázquez et al (2005) in patients with morbid obesity four months after bariatric surgery, which indicated that inflammatory pathways, including the TNF-α system and IL-6, remain activated. However, in 22 obese and 20 hypertensive patients subjected to BT with thermal water at 38 °C in 15 sessions (each of 30-min duration), Oláh et al (2011) observed a significant decrease in post-treatment CRP levels in a hypertensive group but not in obese subjects.…”
Section: Discussionsupporting
confidence: 81%
“…Xydakis et al (2004) found no differences in TNF-α concentrations among obese individuals (56 women and 24 men with a BMI of >(38.3±0.7) kg/m 2 ) after 4-6 weeks of weight loss induced by a very low calorie diet. Perhaps the metabolic stress results from a relative starvation effect on the inflammatory response (Vázquez et al, 2005;Solá et al, 2009). However, Zahorska-Markiewicz et al (2008) reported an impact of weight loss on the level of TNF-α in obese women.…”
Section: Discussionmentioning
confidence: 99%
“…Endothelial dysfunction can be curtailed by nonpharmacological measures, such as physical activity 92 and weight loss, 93 or pharmacological ones, such as statins and angiotensin converting enzyme (ACE) inhibitor. 94 …”
Section: Endothelial Dysfunction and Cardiovascular Disease Predictormentioning
confidence: 99%
“…Disturbed endothelial function can be assessed by measuring the level of these molecules. The concentration of soluble intracellular adhesion molecule-1 (sICAM1) and plasminogen activator inhibitor 1 (PAI-1) have been shown to be the earliest markers of endothelial dysfunction (6,7) and there is evidence that these substances are increased in obese patients (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21).…”
Section: Introductionmentioning
confidence: 99%